The Anatomy Study of the Facial Temporal Region, Age 25–50, in Thai Population Based on Ultrasound Investigation - Chenda Ly; Chantawat Kasemnet; Thamthiwat Nararatwanchai; Tawee Saiwichai; Sirintip Chaichalotornkul (Research Synergy Foundation, 2025)
Aging affects facial tissues, including skin, fat, muscles, and bones, with the temporal region playing a crucial role in both function and appearance. Temporal depression contributes to an aged look, increasing demand for aesthetic procedures. However, the complex layered structure and vascular pathways present challenges for safe interventions in this region. This study utilized high-frequency ultrasound to map the depth and position of the deep temporal arteries and assess the anatomy of the temporal region in Thai individuals aged 25–50 years. The observational cross-sectional design included 33 participants (15.15% male, 84.85% female) with an average age of 33.42 years. High-frequency ultrasound was used to evaluate the soft tissue and artery positioning. The sample included 10 individuals with and 23 individuals without hyaluronic acid filler injections. Significant differences in skin thickness, subcutaneous layers, SMAS layers, temporalis muscle thickness, and temporal bone characteristics were observed between the two groups. Filler injections notably altered anatomical structures, affecting artery depth and position. Despite limitations in sample size and population specificity, the findings underscore the importance of detailed anatomical knowledge for safer and more effective injectable procedures. Ultrasound imaging serves as a healthcare tool in guiding aesthetic interventions in the temporal region.